THE BYZANTINE “ECLOGA” – THE ICONOCLASTIC BREVIARY OF THE JUSTINIAN’S LAWS (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2024)
This paper deals with an important aspect of the legal-historical problem of the famous Byzantine Ecloga  (gr. ΕΚΛΟΓΗ ΤΩΝ ΝΟΜΩΝ; lat. ECLOGA LEGUM – Leonis et Constantini / VIII century), or, translated, The Selection of the Laws of the Eastern Roman Emperors Leo III and his son Constantine V. This imperial legislative work, i.e. imperial breviary or a manual for judicial-administrative practice - which, in the sources, is also found under the name "Isavrian Ecloga" - is, in fact, a kind of abbreviated extract from Justinian's laws, but in a modernized and humanized form. Although the Ecloga starts from the Roman Law, which remained the basis of the Byzantine legal life for ages, it still tries to modify it in the direction of "greater philanthropy", while also adapting it to the social and economic conditions of the time, as well as to the Christian principles. And indeed, analytically speaking, it deviates significantly from the so-called Justinian law - on the one hand, due to the mixtures of church/canon law; and on the other hand, due to the influence of the local Eastern/Asian, i.e. folk customs of the subjects who lived in different parts of the vast Byzantine Empire. More specifically, the author makes an attempt to shed light on a series of significant issues of the ‘legal romanistic’ from the so-called first Byzantine period, that refer to: the importance, the meaning, the authors, the way of creation, the language, the structure/content, the territorial validity and the translations of this post-Justinian legal compilation, submitted during the so-called “heretical emperors”.Finally, we should highlight the fact that, towards the end of the paper, the author makes a pioneering attempt to integrally translate the preface, i.e. the introductory part, that is the "preamble" of the Eclogа – which precedes the normative text, and which is written in a very solemn, panegyric and hymn tone, for the first time in Macedonian language.
Keywords: Ecloga; Byzantine Empire; Justinian's law; Iconoclast Dynasty; titles; Old Slavic law.